All Days 2013
DOI: 10.2118/167057-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water Management Approach for Shale Operations in North America

Abstract: This paper discusses technical drivers that influence the produced/flowback water management goals and decisions in unconventional hydrocarbon developments and then presents case studies and a decision tree chart for effective water treatment. Produced/flowback water quality in shale projects is influenced not only by the formation, but also by the fracturing fluid introduced to the formation during hydraulic stimulation. The water produced by shale wells can contain suspended solids, dissolved solids, organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Direct reuse, whereby produced water is directly blended with freshwater before formulation of the fracturing fluid, results, by and large, in the lowest treatment costs but greater chemical costs for fluid formulation and perhaps a decline in the well's production. Increased costs associated with reuse, depending on the degree of treatment employed, can come in the form of: increased friction reducer and scale inhibitor demand with high chloride contents; increased scaling within the shale formation with the presence of divalent ions; increased corrosion of pipes; increased levels of sulphate reducing bacteria resulting in the production of H 2 S gas [8]; and a reduction in the performance of coagulation/flocculation, flotation, gravity settling and plate and frame dewatering equipment due to residual unbroken polymer gel [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct reuse, whereby produced water is directly blended with freshwater before formulation of the fracturing fluid, results, by and large, in the lowest treatment costs but greater chemical costs for fluid formulation and perhaps a decline in the well's production. Increased costs associated with reuse, depending on the degree of treatment employed, can come in the form of: increased friction reducer and scale inhibitor demand with high chloride contents; increased scaling within the shale formation with the presence of divalent ions; increased corrosion of pipes; increased levels of sulphate reducing bacteria resulting in the production of H 2 S gas [8]; and a reduction in the performance of coagulation/flocculation, flotation, gravity settling and plate and frame dewatering equipment due to residual unbroken polymer gel [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the challenges faced in reuse can be dealt with through primary treatment that removes suspended solids, oil, iron, unbroken polymers and bacteria [9], generally at a cost much below complete desalination (circa $1/bbl ($6.3/m 3 ) compared to $3.50-6.25/bbl ($22-39/m 3 ) for complete desalination [1]). The need for the removal of all solids, suspended and dissolved, is less clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water management and its impact on unconventional reservoir economics is a key focus area for the industry these days. Slutz et al (2012), Fedotov et al (2013) have highlighted the issues at hand and suggested possible best practices. On an average less than 25% of stimulation water is ever recovered back in most of the contemporary unconventional reservoirs under development (Pagels et al, 2012).…”
Section: Introductionmentioning
confidence: 99%